2022
DOI: 10.1007/s10571-022-01261-0
|View full text |Cite
|
Sign up to set email alerts
|

Genes of the Ubiquitin Proteasome System Qualify as Differential Markers in Malignant Glioma of Astrocytic and Oligodendroglial Origin

Abstract: We have mined public genomic datasets to identify genes coding for components of the ubiquitin proteasome system (UPS) that may qualify as potential diagnostic and therapeutic targets in the three major glioma types, astrocytoma (AS), glioblastoma (GBM), and oligodendroglioma (ODG). In the Sun dataset of glioma (GEO ID: GSE4290), expression of the genes UBE2S and UBE2C, which encode ubiquitin conjugases important for cell-cycle progression, distinguished GBM from AS and ODG. KEGG analysis showed that among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 154 publications
(154 reference statements)
0
4
0
Order By: Relevance
“…Given that IDH -mutated and IDH wildtype gliomas display distinct mutation profiles and clinical trajectories, they are considered to develop through separate oncogenic mechanisms, thus representing distinct entities despite their histopathological similarities [ 20 ]. A study by Vriend and Klonisch presents evidence indicating that contributions from genes in the ubiquitin proteasome system (UPS) to the Notch and Hippo pathway signatures are interconnected with stem cell pathways and possess the capability to differentiate GBM from AS and ODG [ 21 ]. Their analysis revealed that AURKA and TPX2 (two cell-cycle genes encoding for E3 ligases, as well as the cell-cycle gene responsible for encoding the E3 adaptor CDC20) are upregulated in GBM.…”
Section: Genetic Landscape Of Gliomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that IDH -mutated and IDH wildtype gliomas display distinct mutation profiles and clinical trajectories, they are considered to develop through separate oncogenic mechanisms, thus representing distinct entities despite their histopathological similarities [ 20 ]. A study by Vriend and Klonisch presents evidence indicating that contributions from genes in the ubiquitin proteasome system (UPS) to the Notch and Hippo pathway signatures are interconnected with stem cell pathways and possess the capability to differentiate GBM from AS and ODG [ 21 ]. Their analysis revealed that AURKA and TPX2 (two cell-cycle genes encoding for E3 ligases, as well as the cell-cycle gene responsible for encoding the E3 adaptor CDC20) are upregulated in GBM.…”
Section: Genetic Landscape Of Gliomasmentioning
confidence: 99%
“…Their analysis revealed that AURKA and TPX2 (two cell-cycle genes encoding for E3 ligases, as well as the cell-cycle gene responsible for encoding the E3 adaptor CDC20) are upregulated in GBM. Further, genes associated with E3 ligase adaptors, exhibiting differential expression, demonstrated a significant overrepresentation in the Hippo pathway, contributing to the distinction of classic, mesenchymal, and proneural subtypes of GBM [ 21 ].…”
Section: Genetic Landscape Of Gliomasmentioning
confidence: 99%
“…Interestingly, FoxM1 is upregulated in brain tumors, particularly GB and meningioma [75,106]. Upregulation of UBE2C is observed in GB tissues, mainly in the proneural subtype, characterized by neurogenesis-related gene expression and increased invasion [107,108]. The combined upregulation of UBE2C and aurora kinase B (AURKB), an important player in the cell cycle, is associated with a dismal outcome, therapeutic resistance, and reduced overall survival in glioma patients [76].…”
Section: Ube2c and Brain Cancer Invasion And Disseminationmentioning
confidence: 99%
“…Multiple studies have shown that GBM cells exhibit changes in the expression of genes associated with UPS [ 13 , 14 ]. Ubiquitin, a highly conserved protein with a length of 76 amino acids, is expressed in all cell types and ubiquitination, the attachment of ubiquitin to a substrate, is one of the most common post-translational modifications of proteins.…”
Section: Ups Molecular Components and Functions In Cell Survival Show...mentioning
confidence: 99%